Therapeutic Effect of Ginsenoside Rd on Experimental Autoimmune Encephalomyelitis Model Mice: Regulation of Inflammation and Treg/Th17 Cell Balance - Bo Jin; Chixiao Zhang; Yu Geng; Mei Liu (Mediators of Inflammation)
Multiple sclerosis (MS) is an autoimmune inflammatory disease. Inflammatory infiltrates and demyelination of the CNS are the major characteristics of MS and its related animal model-experimental autoimmune encephalomyelitis (EAE). Immoderate autoimmune responses of Th17 cells and dysfunction of Treg cells critically contribute to the pathogenesis of MS and EAE. Our previous study showed that Ginsenoside Rd effectively ameliorated the clinical severity in EAE mice, but the mechanism remains unclear. In this study, we investigated the therapeutic effect of Ginsenoside Rd on EAE in vivo and in vitro and also explored the potential mechanisms for alleviating the injury of EAE. The results indicated that Ginsenoside Rd was effective for the treatment of EAE in mice and splenocytes. Ginsenoside Rd treatment on EAE mice ameliorated the severity of EAE and attenuated the characteristic signs of disease. Ginsenoside Rd displayed the therapeutic function to EAE by modulating inflammation and autoimmunity, via the downregulation of related proinflammatory cytokines IL-6 and IL-17, upregulation of inhibitory cytokines TGF-β and IL-10, and modulation of Treg/Th17 imbalance. And the Foxp3/RORγt/JAK2/STAT3 signaling was found to be associated with this protective function. In addition, analysis of gut microbiota showed that Ginsenoside Rd also had modulation potential on gut microbiota in EAE mice. Based on this study, we hypothesize that Ginsenoside Rd could be a potential and promising agent for the treatment of MS.